Analisis Kontribusi Penyertaan Modal dan Dividen pada Badan Usaha Milik Daerah di Kota Kupang - Grachella Putri Sthivania; Sarlin Paleina Nawa Pau; Indah Mutiara (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to analyze the contribution of regional government capital participation to the dividends distributed by Regional-Owned Enterprises (BUMD) in the city of Kupang. This research employs a mixed-method approach using secondary data in the form of Budget Realization Reports (APBD) from 2018 to 2024 and BUMD dividend data, as well as primary data obtained through interviews with the Finance and Regional Asset Agency of Kupang City. The analysis is conducted quantitatively with descriptive methods by calculating the Return on Investment (ROI) and comparing the amount of capital participation with the dividends, complemented by qualitative data from the interview results. The findings indicate that Bank NTT consistently realizes capital participation and regularly distributes dividends with a fairly good ROI, whereas PD Pasar contributes relatively small dividends, and KPN Maju does not distribute dividends at all. The study concludes that the capital participation of Kupang City Government has not been fully effective in increasing the Local Original Revenue (PAD), thus requiring more selective and performance-based investment management